(untitled) (Bangladesh Journal of Botany, 2010)
Phosphorus deficiency resulted in an increase in the length of primary root, length and number of lateral roots, root hairs and root meristem volume of the seedlings of lentil grown in rhizobox. Key words: Phosphorus deficiency; Root length; Root growth; Rhizobox; Lentil DOI: 10.3329/bjb.v38i2.5153 Bangladesh J. Bot. 38(2): 215-218, 2009 (December)